Market Proximity, Income, and Home Gardening: Investigating Determinants of Household Food Security for Young Children in Samarinda City (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Food insecurity remains a significant public  health issue, especially among infants and young children. This study  aimed  to  identify  the  determinants  of  food  security  among 6-23-month-old  infants  in  Mangkupalas, Samarinda,  Indonesia.  A  cross-sectional  study  was  conducted  among  137  households  with  infants  aged  6-23 months in Puskesmas Mangkupalas area. The study used consecutive sampling in 3 villages namely tenun, mesjid and mangkupalas.  Quantitative  data  were  collected  using  a  structured  questionnaire  and  analyzed  using spearman  rank  correlation  test.A  total  of  73.7%  of  households  locatednear  markets  were  food  secure compared  to  52.5%  of  those  far  from  markets,  and  this  distance  was  statistically  associated  with  household food security(p = 0.019, r = -0.201). Household income showed a significant positive association with food security (p = 0.008, r = 0.226), where 76.7% of households earning ≥3,500,000 IDR/month were food secure compared to only 52.2% among those earning ≤1,500,000 IDR/month.  Interestingly,  home  gardening,  which  theoretically influences food security, was not found to have a significant association(p = 0.884, r = 0.017).The findings indicate that  in  urban areas, where  food  access  heavily  depends  on  purchasing  power  and  proximity  to  food  sources, household food security is shaped more by economic stability and market access than by subsistence practices like home gardening. Limited land availability and a narrow variety of cultivated crops may constrain the effectiveness of home gardening in contributing to nutritional adequacy.